Pseudomonas aeruginosa Alkyl quinolones repress hypoxia-inducible factor 1 (HIF-1) signaling through HIF-1a degradation - Legendre, C.; Reen, F.; Mooij, M.; McGlacken, G.; Adams, C.; O'Gara, Fergal (American Society for Microbiology, 2012)
The transcription factor hypoxia-inducible factor 1 (HIF-1) has recently emerged to be a crucial regulator of the immune response following pathogen perception, including the response to the important human pathogen Pseudomonas aeruginosa. However, as mechanisms involved in HIF-1 activation by bacterial pathogens are not fully characterized, understanding how bacteria and bacterial compounds impact on HIF-1α stabilization remains a major challenge. In this context, we have focused on the effect of secreted factors of P. aeruginosa on HIF-1 regulation. Surprisingly, we found that P. aeruginosa cell-free supernatant significantly repressed HIF-1α protein levels. Further characterization revealed that HIF-1α downregulation was dependent on a subset of key secreted factors involved in P. aeruginosa pathogenesis, the 2-alkyl-4-quinolone (AQ) quorum sensing (QS) signaling molecules, and in particular the pseudomonas quinolone signal (PQS). Under hypoxic conditions, the AQ-dependent downregulation of HIF-1α was linked to the suppressed induction of the important HIF-1 target gene hexokinase II. Furthermore, we demonstrated that AQ molecules directly target HIF-1α protein degradation through the 26S-proteasome proteolytic pathway but independently of the prolyl hydroxylase domain (PHD). In conclusion, this is the first report showing that bacterial molecules can repress HIF-1α protein levels. Manipulation of HIF-1 signaling by P. aeruginosa AQs could have major consequences for the host response to infection and may facilitate the infective properties of this pathogen.